Diversity, abundance, and evenness of lizards and snakes (Reptilia: Squamata) in Winongo River, Province of DIY - Yudha, Donan Satria; Eprilurahman, Rury; Fauzi, Luthfi; Hanik, Nureini; Desmi, Nola; Putra, Rachmat Aditama Dwija; Erieco, Luthfi (Generasi Biologi Indonesia, 2025)
River is one of the habitats for reptiles. Based on the research along Code River, Opak River and Gadjahwong River, reptiles commonly found along rivers in Yogyakarta were lizards and snakes. Research on lizards and snakes’ diversity is essential to know its diversity and to understand its habitat along rivers in Yogyakarta. Methods used was Visual Encounter Survey combined with time search. Data analyzed using Shannon-Wiener Index, Pielou Evenness Index and degree of abundance based on Buden (2000). Result obtained were lizards 9 species and 15 snakes’ species. Lizard diversity based on Shannon-Wiener Index, on upstream, midstream and downstream were categorized as low with H’ 0,246; 0,228 and 0,185 respectively. Snake diversity based on Shannon-Wiener Index, on upstream was low with H’: 0,099; on midstream and downstream were moderate with H’: 0,182 and 0,135. Lizard evenness based on Pielou Index, on upstream, midstream and downstream were categorized as low with E 0,178; 0,127 and 0,115 respectively. Snake evenness based on Pielou Index, on upstream, midstream and downstream were also categorized as low with E 0,099; 0,182 and 0,135 respectively. Most abundant lizards were: Eutropis multifasciata and Bronchocela jubata, meanwhile most abundant snakes were: Dendrelaphis pictus, Ahaetulla prasina, and Homalopsis buccata.